Foam concrete production with şırnak mine waste claystone and fly ash - Tosun, Yıldırım İsmail (IOS Press, 2014)
Fly ash and Mine Waste clay stone thrown as waste in Şırnak City of Turkey were used in foam concrete production. Waste mixture at certain proportions decreasing instead of cement used, fine aggregate in specific proportions decreasing instead of fly ash used improved mechanical strength and porosity. Even fine clay stone aggregate minus 3 mm reducing porosity rather than fly ash, such as using three different size fractions are evaluated in foam concrete production. Effects of mechanical properties of waste clay stone and fly ash on foam concrete production were studied intensively. The main purpose of this study is to develop the ready-mixed foam mortar and concrete industry using local waste, Şırnak Coal Mine Waste clay stone and fly ash.
Keywords: Foam concrete; lightweight concrete; foam mortar; fly ash; claystone